Associated Factors of Low Back Pain in a Sample of Patients Attending Hawler Teaching Hospital/Erbil City A Case Control Group (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Background and objective: Low back pain (LBP) is an important clinical, social, economic, and public health problem affecting the population erratically and random. The aim of the study was to determine the factors associated with low back pain among patients attending physiotherapy department at Hawler teaching hospital in Erbil City.Methods: the study was carried out from November 3rd, 2014 to November 3rd 2015.The study involved of 100 cases diagnosed with low back pain in the physiotherapy depart- ment at Hawler teaching hospital subjects in control group are of the same age and gender of those in the experiment group , and 100 participants as a 100 as control group free from low back pain.Result: Multiple logistic regression of risk factors of low back pain revealed that body mass index7.55 , non using lumbar support in sitting chair during work31.81, non-practice exercise 5.58, standing erect 34.836, sitting on a high backrest chair 27.986, sitting on a low backrest chair 65.167, drinking water per day 18.989, emotional stress 14.636 time have risky effect on low back affect low back pain respectively.Conclusion: The study concluded that most of the participants in the study were employers and they perform different types of positions such as bending, squatting and sitting during work time, there were statistical significant association between body mass index, lifting heavy objects, driving and emotional stress with development of low back pain